(untitled) (Semiárida, 2020)
The values of green biomass (Bv) measured in a grassland were associated with index values of normalized difference vegetation index (NDVI) from satellite data in three relict natural grassland on stream Chucul, from his beginning site 1 (32° 49’21, 0” S and 64° 24`07.0”W) until its demise in plain area: site 3 (33° 06` 25.5`` S and 63° 32`49.1`` W). Under the hypothesis of correspondence of Bv and data obtained by images, the aim of this work is to determine the relationship between measured field data and satellite data in natural grasslands. Seasonally during the 2009-2011 cycle were sampled at random with 10 replicates of 0.25 m2 recording floristic list. To determine Bv in each plot the biomass was cut and separated in green and dry compartments and dryed to constant weight. For digital analysis bands 3 and 4 of Landsat 5 TM image (Path 228 Row 083) were used for each site close to the sampling date. The highest values of green biomass were determined for site 3, in December 2011: 189.6 g/m2 and in March for sites 1 and 2: 105.74 and 115.22 g/m2. Among all the observed values of biomass and NDVI estimated the correlation coefficient was highest at site 3 (R= 0.50). The results of the work for site 3 validate the hypothesis and indicats of the aptitude of digital images for study the status and changes in vegetation.